2019
DOI: 10.1001/jamanetworkopen.2019.13249
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in 30-Day Hospital Readmissions Among US Adults With Diabetes

Abstract: Key PointsQuestionAre there differences in hospital readmission rates among racial and ethnic minorities with diabetes, and if so, what are the individual-level and hospital-level factors associated with these differences?FindingsIn this cohort study of 272 758 adults with diabetes, black patients had a significantly higher risk of unplanned all-cause 30-day hospital readmission than members of other racial/ethnic groups. This difference was most pronounced among lower-income patients and patients hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 37 publications
3
29
1
Order By: Relevance
“…African American race patients were also found to have a higher LOS. These results are consistent with findings from other studies [ 13 - 15 ]. This may reflect differences in access to care and socioeconomic status and points to a higher risk population for which additional safeguards should be considered to maintain a safe discharge.…”
Section: Discussionsupporting
confidence: 94%
“…African American race patients were also found to have a higher LOS. These results are consistent with findings from other studies [ 13 - 15 ]. This may reflect differences in access to care and socioeconomic status and points to a higher risk population for which additional safeguards should be considered to maintain a safe discharge.…”
Section: Discussionsupporting
confidence: 94%
“…This contrasted with white men who had a higher proportion of hospitalizations compared to white women. Our findings are in concert to a recent evaluation of rehospitalization [ 20 ]. Black patients had a higher risk of readmission compared with white patients (OR, 1.15; 95% CI, 1.12–1.18; P ​< ​0.001), An administrative claims data set of commercially insured and Medicare Advantage beneficiaries across the United States was used.…”
Section: Discussionsupporting
confidence: 88%
“…Race and racism are a public health issue. We already knew this through numerous studies that have found Black Americans have worse outcomes in conditions as broad as diabetes, 11 hypertension, 12 pregnancy‐related mortality, 13 injury from legal interventions, 14 and even oral health 4 . In 2020, the American Medical Association enacted a policy that acknowledges racism is a public health issue 15 .…”
Section: Introductionmentioning
confidence: 99%